2020
DOI: 10.1001/jamanetworkopen.2020.8759
|View full text |Cite
|
Sign up to set email alerts
|

Global Burden of Thyroid Cancer From 1990 to 2017

Abstract: IMPORTANCE Thyroid cancer is the most pervasive endocrine cancer worldwide. Studies examining the association between thyroid cancer and country, sex, age, sociodemographic index (SDI), and other factors are lacking. OBJECTIVE To examine the thyroid cancer burden and variation trends at the global, regional, and national levels using data on sex, age, and SDI. DESIGN, SETTING, AND PARTICIPANTSIn this cross-sectional study, epidemiologic data were gathered using the Global Health Data Exchange query tool, cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
169
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(181 citation statements)
references
References 45 publications
9
169
1
2
Order By: Relevance
“…Differentiated thyroid cancer (DTC) is the most common endocrine malignancy [ 1-3 ], and its incidence has been increasing over the last 40 years [ 1-4 ]. The widespread use of neck ultrasonography and other imaging studies has contributed significantly to the detection of a significant number of these cases that would otherwise have remained undiscovered [ 3 , 5 ]. The majority of cases are small papillary thyroid cancer (PTC) with low risk for recurrence and mortality [ 3 , 5-7 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Differentiated thyroid cancer (DTC) is the most common endocrine malignancy [ 1-3 ], and its incidence has been increasing over the last 40 years [ 1-4 ]. The widespread use of neck ultrasonography and other imaging studies has contributed significantly to the detection of a significant number of these cases that would otherwise have remained undiscovered [ 3 , 5 ]. The majority of cases are small papillary thyroid cancer (PTC) with low risk for recurrence and mortality [ 3 , 5-7 ].…”
mentioning
confidence: 99%
“…The widespread use of neck ultrasonography and other imaging studies has contributed significantly to the detection of a significant number of these cases that would otherwise have remained undiscovered [ 3 , 5 ]. The majority of cases are small papillary thyroid cancer (PTC) with low risk for recurrence and mortality [ 3 , 5-7 ]. Studies over the last decade have shown that less than 30% of cases of DTC are high risk, whereas the majority are low and intermediate risk [ 8-11 ].…”
mentioning
confidence: 99%
“…The incidence of TC in China is also significantly different based on gender and age. Therefore, more evidence-based studies are required to confirm the existing findings regrading TC trends in these countries [ 1 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…which is the least square method for the measured result yi,j and the calculated result fi,j; NS and ND are the numbers of the sources and detection fibers used in measurements, respectively; Hi,j = 1 except for seven source-detection combinations that were excluded due to insufficient SNR. For the excluded pairs (i, j) = (2, 1), (2,6), (3,3), (3,8), (5,1), (5,6), and (7,6), Hij = 0. We used Tikhonov regularization, and τ is the hyper parameter; NR is the number of points of the reconstructed grid used to solve the inverse problem.…”
Section: Inverse Problemmentioning
confidence: 99%
“…The incidence of thyroid cancer has been increasing in many parts of the world over the past decades, although thyroid cancer remains among the less common cancers [1,2]. The etiology of the increasing incidence is not established.…”
Section: Introductionmentioning
confidence: 99%